Cleaning capacity of octenidine as root canal irrigant: A scanning electron microscopy study - Coaguila-Llerena, Hernán [UNESP]; Stefanini da Silva, Virgínia [UNESP]; Tanomaru-Filho, Mario [UNESP]; Guerreiro Tanomaru, Juliane Maria [UNESP]; Faria, Gisele [UNESP] (Wiley, 2018)
The aim of this study was to assess the cleaning capacity of the octenidine hydrochloride (OCT) used as root canal irrigant by scanning electron microscopy (SEM) analysis. Sixty human unirradicular extracted teeth were randomly distributed in 6 groups (n = 10) according to irrigant solutions which were used during root canal preparation: G1, 0.1% OCT; G2, 2% chlorhexidine (CHX); G3, 2.5% sodium hypochlorite (NaOCl); G4, OCT + 17% ethylenediaminetetraacetic acid (EDTA); G5, 2.5% NaOCl + 17% EDTA and G6, distilled water. All specimens were instrumented with ProTaper system up to F4. Teeth were sectioned and prepared for SEM. The smear layer was evaluated using a 5-score system and the data were analyzed by Kruskal–Wallis and Dunn (α = 0.05). In all root canal thirds there was no significant difference between OCT, CHX, NaOCl, and water groups (p >.05), and these groups showed higher smear layer values than NaOCl + EDTA and OCT + EDTA groups (p <.05). There was no significant difference between NaOCl + EDTA and OCT + EDTA groups (p >.05). It was concluded that OCT used as a single root canal irrigant presented poor cleaning capacity and could be used in association with a final irrigation with EDTA to obtain smear layer removal.
Keywords: chlorhexidine; octenidine hydrochloride; smear layer; sodium hypochlorite